The Influence of Place on Weight Gain during Early Childhood: A Population-Based, Longitudinal Study - Carter, Megan A.; Dubois, Lise; Tremblay, Mark S.; Taljaard, Monica (Université d'Ottawa | University of Ottawa, 2012)
The objective of this paper was to determine the influence of place factors on weight gain in a contemporary cohort of children while also adjusting for early life and individual/family social factors. Participants from the Québec Longitudinal Study of Child Development comprised the sample for analysis (n=1,580). A mixed-effects regression analysis was conducted to determine the longitudinal relationship between these place factors and standardized BMI, from age 4 to 10 years. The average relationship with time was found to be quadratic (rate of weight gain increased over time). Neighborhood material deprivation was found to be positively related to weight gain. Social deprivation, social disorder, and living in a medium density area were inversely related, while no association was found for social cohesion. Early life factors and genetic proxies appeared to be important in explaining weight gain in this sample. This study suggests that residential environments may play a role in childhood weight change; however, pathways are likely to be complex and interacting and perhaps not as important as early life factors and genetic proxies. Further work is required to clarify these relationships.
Keywords: Children; Neighborhood; Residential characteristics; Environment; Body weight; Body mass index; Longitudinal study; Mixed-models; Social factors